Synthesis, Characterization and Adsorption Properties of the New Chitosan/Natural Zeolite Composite for the Nitrate Removal from Aqueous Solution - Toktam Shenavaei -Zare; Zahra-Beagom Mokhtari-Hosseini (Journal of Chemical and Petroleum Engineering)
High concentrations of nitrates in water can have several effects on human and aquatic health, therefore, control levels of nitrates are essential. In this work, the adsorption of nitrate on beads of chitosan and zeolite composites was investigated. According to Transmission Electron Microscopy results, the employed zeolite has clinoptilolite and calcite with 50-870 nm particle size. The association between chitosan and zeolite was also verified by chemical and morphological characterizations. Results showed chitosan/acid-modified natural zeolite composite beads (Ch/AMZ) exhibited higher nitrate adsorption than other ones. The nitrate adsorption on Ch/AMZ as a function of pH, contact time, and bead concentration was optimized by a response surface method using batch experiments. According to the results, at the computed optimum operating conditions the maximum nitrate removal efficiency, 98.2% with Ch/AMZ, and adsorption capacity, 22.48 mg g−1 were obtained. The presented nitrate removal technique with the proposed eco-friendly adsorbent can be considered a critical approach for removing nitrate from drinking water and possibly using it on an industrial scale as a green and economical method for water and wastewater treatment.